Pontarachnid mites from marine interstitial, with a description of three new species from South Korea (Acari: Hydrachnidia: Pontarachnidae) - Pešić, Vladimir (Zootaxa, 2013)
Most of the known pontarachnid species (Acari, Hydrachnidia) live in the marine littoral zone; a few species have been described from freshwaters, but these species were found to occur in estuaries or locations near the sea. Occasionally some specimens of the surface dwelling species were taken from marine interstitial. During a recent survey on marine interstitial fauna along the coast of South Korea, some pontarachnid mites were collected. Three species, i.e., Pontarachna ivonae sp. nov. (Yellow Sea and East Sea), Litarachna lukai sp. nov. (Yellow Sea) and L. gracilis sp. nov. (East Sea) are described as new to science. Two latter species have reduced eye pigmentation indicating that they can be the first representatives of the interstitial pontarachnid mites.